Shinzo Abe y la dialéctica política exterior-política interna. La agenda estadounidense en la política japonesa - Ramírez Bonilla, Juan José (El Colegio de México A.C., 2014)
The paper analyzes the repercussions of a foreign policy defined by the strategic alliance with the U.S. government on the domestic policies of the Shinzo Abe government. The Japanese electorate voted the Democratic Party of Japan (dpj) into power with a majority in the House of Representatives, enabling them to form a government. Subsequently, the combination of foreign policy issues connected with the U.S. redeployment in the Far East and the crisis of the Senkaku/Diaoyu islands, the electorate returned the Liberal Democrat Party (ldp) to power. The government of Shinzo Abe had repercussions on foreign policy issues that weakened the dpj; these issues could turn against the ldp; they may put an end to the privileges of sectors the party has traditionally patronized.